Pertanggung jawaban Pidana Korporasi dalam Tindak Pidana Korupsi di Indonesia - Tiara Jelita Andalusianti Roozan; Rajwa Al Imtiyaz; Hasrinda Rizqi Pramassari; Muhammad Reyvanza Anwar (Pusat Riset dan Inovasi Nasional, 2025)
This article analyzes the juridical construction, practical implementation, and problematics of corporate criminal liability in corruption cases in Indonesia. Employing a normative-juridical approach with analytical-evaluative dimensions, this research examines primary, secondary, and tertiary legal materials, as well as data from in-depth interviews with key informants. The results indicate that despite the legal framework accommodating the concept of corporations as subjects of criminal law in corruption cases, its implementation faces significant obstacles reflected in the minimal designation of corporations as suspects/defendants. These obstacles encompass substantive aspects related to unclear formulation of liability elements, procedural aspects concerning limitations in procedural law, institutional aspects regarding law enforcement capacity, and practical aspects related to sanctions execution. This research proposes a comprehensive and integrative model for strengthening corporate criminal liability through normative reformulation, procedural and institutional strengthening, and development of corporate compliance incentives, projected to contribute to improving the effectiveness of corporate corruption enforcement and strengthening business integrity systems in Indonesia.